Methylation Mediated Silencing of miR-155 Suppresses the Development of Preeclampsia In Vitro and In Vivo by Targeting FOXO3. (26th May 2022) - Luo, Xiaohua; Pan, Ci; Guo, Xiaopei; Gu, Cunhua; Huang, Yulian; Guo, Jing; Zeng, Ying; Yue, Jinjing; Cui, Shihong
Abstract : Preeclampsia (PE) is a common pregnancy-related syndrome characterized by chronic immune activation. This study is aimed at exploring the role of miR-155 in the inflammatory pathogenesis of PE. Placental tissues and peripheral blood were collected from all subjects. BSP detection analysis was performed to evaluate miR-155 methylation levels. ELISA was performed to measure the levels of inflammatory cytokines and MMP2 in serum samples and cellular supernatants. HTR-8/SVneo and JEG-3 cells were transfected with miR-155 mimic and the inhibitor to establish the overexpressed miR-155 and silenced miR-155 cell models, respectively. Treatment with 5-Aza was performed to alter the DNA methylation level of miR-155. The PE rat model was established after subcutaneous injection of NG-nitro-L-arginine methyl ester. The CCK-8 assay, TUNEL staining, and Transwell assay were performed. Reverse transcription-quantitative PCR, Western blot analysis, and immunohistochemical assay were used to analyze related gene expression levels. The luciferase reporter assay was used to investigate the direct interaction between FOXO3 and miR-155. Results showed that miR-155 was remarkably upregulated and inversely correlated with the promoter methylation level in the placental tissue from PE patients. The in vitro experiments indicated that miR-155 decreased viability, migration, and invasion, but increased apoptosis in trophoblast cells. FOXO3 was confirmed as the target of miR-155. Transfection of the miR-155 inhibitor suppressed inflammation and oxidative stress, but elevated proliferation, migration, and invasion of trophoblast cells, which were abolished by 5-Aza treatment or cotransfection with si-FOXO3. In summary, our data suggested that methylation-mediated silencing of miR-155 can inhibit the apoptosis, inflammation, and oxidative stress of trophoblast cells by upregulating FOXO3.